A Feast or a Threat? Multi-Mycotoxin Contamination in Sun-Dried Fish, Collected from Al Mukha Markets, Taiz, Yemen - Al-Jobory, Hala J. (PSM Microbiology, 2025)
In the bustling fish markets of Yemen, where sun-dried Wazef has nourished generations, our study uncovered a troubling paradox beneath its protein-rich surface. Analysis of 20 samples revealed excellent nutritional quality (47.07% protein, 22.48% lipids, 9.34% moisture), yet all carried an alarming burden of toxic fungi. Among 142 fungal isolates tested, 66 (46.5%) produced mycotoxins, with Aspergillus (67%) and Penicillium (24.7%) species predominating. Alarmingly, we detected multiple mycotoxins in 95% of samples, including co-occurrence of aflatoxins (B1, B2, G1, G2) in 40% of samples, often alongside Citrinin (30%), Ochratoxin A (20%), and Sterigmatocystin (30%). The most prolific producers were A. flavus (55.6% toxigenic) and P. citrinum (76.9% toxigenic), which also exhibited potent enzymatic activity (protease: 78%; lipase: 89.4%). This widespread multi-mycotoxin contamination, combined with the spoilage potential of fungi, creates a perfect storm of nutritional degradation and health risks. Our findings expose a critical paradox: a food designed to sustain coastal communities may instead jeopardize their health through chronic exposure to carcinogenic compounds. The study sounds an urgent alarm for implementing controlled drying technologies and stricter food safety measures to preserve both the nutritional benefits and safety of this culturally vital food source.